Factors influencing the establishment of schools of allied health professions - Trinidad and Tobago - Bernard, John Adrian (1979)
This study investigated the factors influencing the establishment of a Regional College of Allied Health Sciences in Trinidad and Tobago. The experiences of selected countries in both the developed and developing world, in the area of training of allied health clinicians and the utilization of their services, were compared to efforts made in Trinidad and Tobago. Data were collected through a questionnaire completed by a sample of 180 persons made up of students from developing countries undergoing training in allied health at the University of Pittsburgh and Carlow College in Pittsburgh, faculty members at these facilities associated with allied health education and training in developing countries, students and faculty in allied health training in Trinidad and Tobago, administrators at the Ministry of Health in Trinidad and Tobago, and the faculty members of the UNDP/WHO/PAHO training school in Barbados. The findings indicated that the same factors which influenced the development of education and training facilities for allied health clinicians in other developing countries would influence the efforts to raise the standard of allied health care in Trinidad and Tobago. Among these factors, economics appeared to be the most significant. It was suggested that in order to increase the likelihood of a positive result of the efforts to establish the college, and to ensure some degree of acceptance of the graduates, the sponsoring agency, faculty, students, staff, and groups of practising allied health clinicians needed to aim towards professionalizing the discipline and occupation of allied health
Keywords: Professional education